STEAM VALVE WITH VARIABLE OPERATING FORCE - SUTEFUAN ROBAATO PURINSU; JIEEMUSU MAATEIN SUDORUNIKU (1991)
PURPOSE: To reduce valve actuating force past a cracking position by forming two types of effective diameters of a balance cylinder and a balance piston, respectively. CONSTITUTION: In this steam valve 56, two types of effective diameters are formed out of an inner-periphery surface 62 and an inward flange 72 at a balance cylinder 64, and two types of effective diameters are formed out of a larger diameter outer-periphery part 68 and a smaller diameter outer-periphery part 70 at the sleeve 66 of a balance piston 58. When a main valve 12 and the balance piston 58 move upward past a cracking position, the smaller diameter outer-periphery part 70 faces the inward flange 72, and a sealing flange 60 faces the inner-periphery surface 62. As a result, steam can pass through without the inward flange 72 being restrained, the differential pressure which supports upward balance force acts on the whole relatively wide area determined by the sealing flange 60. It is thus possible to exert larger balance force by a steam valve 56 past the cracking position, thereby reducing valve actuating force.